Body Morphology and Drag in Swimming: CFD Analysis of the Effects of Differences in Male and Female Body Types - Andrew X. G. Wang; Zbigniew J. Kabala (Fluids, 2022)
This study analyzes the effect of the morphological characteristics of swimmers on passive drag and determines whether the female or male body type is more efficient for gliding. As a result of puberty, males and females develop different body structures; this study investigates whether these changes in shape influence drag. Computational fluid dynamics (CFD) simulations carried out in Ansys Fluent software were used to calculate the drag force and coefficient from 2D models of swimmers in streamline position, generated based on common anthropometric measurements. Both the top and side view profiles of the swimmers were simulated, unique to this study. The normalized male and female body shapes were simulated at different velocities, and it was demonstrated that the male body shape has a lower drag coefficient than the female body shape by 10.1% and 2.8% for top view and side view profiles, respectively. The in-depth analysis and simulation of models with varying hip and chest dimensions found a significant and positive correlation between hip and chest size and drag, with the chest size having the largest effect of an average 12.2% increase in drag per 5% increase in chest breadth. The results from modifying anthropometric variables explain the discrepancy between the drag experienced by male and female swimmers and show that enlarged hips and chests cause an increase in resistance. The differences between drag for males and females were found to be comparable to the 6.2% and 7.7% drag differences between full-body fastskin and normal suits, indicating measurable impact on performance. These findings suggest that the morphology of swimmers does have a significant effect on drag and that the male body shape is more hydrodynamic than the female body shape.